2021
DOI: 10.1101/2021.09.12.21263445
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Age-specific effects of childhood Body Mass Index on multiple sclerosis risk

Abstract: Objective Higher childhood Body Mass Index (BMI) during early life is thought to be a causal risk factor for Multiple Sclerosis (MS). We used longitudinal mendelian randomisation (MR) to determine whether there is a critical window during which BMI influences MS risk. Methods Summary statistics for childhood BMI and for MS susceptibility were obtained from recent large GWAS. We generated exposure instruments for BMI during four non-overlapping epochs (< 3 months, 3 months - 1.5 years, 2 - 5 years, and 7… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
1
0
2
Order By: Relevance
“…Here, a number of reports, relying on different methods, suggest that genetic risks spanning childhood, adolescence and early adulthood likely comprise a combination of age-specific and age-invariant influences. For example, several studies have shown that the PRS for childhood BMI predicts adult BMI, metabolic outcomes and other complex traits [80][81][82][83][84]. Other studies relying on twin data have reported genetic correlations between BMI assessed at shorter age intervals spanning infancy, adolescence and teenage years that are much higher compared to genetic correlations based on wider age intervals [8,14,85,86].…”
Section: Plos Geneticsmentioning
confidence: 99%
“…Here, a number of reports, relying on different methods, suggest that genetic risks spanning childhood, adolescence and early adulthood likely comprise a combination of age-specific and age-invariant influences. For example, several studies have shown that the PRS for childhood BMI predicts adult BMI, metabolic outcomes and other complex traits [80][81][82][83][84]. Other studies relying on twin data have reported genetic correlations between BMI assessed at shorter age intervals spanning infancy, adolescence and teenage years that are much higher compared to genetic correlations based on wider age intervals [8,14,85,86].…”
Section: Plos Geneticsmentioning
confidence: 99%
“…Перспективним напрямком є дослідження впливу конституціональних особливостей будови тіла на розвиток та перебіг множинного склерозу [14]. Виявлення таких показників, асоційованих з виникненням та особливостями перебігу множинного склерозу, дозволить покращити діагностику на доклінічній фазі та більш ефективно обирати лікувальну стратегію.…”
Section: вступunclassified
“…Використовуючи модель випадок-контроль, досліджувався комбінований зв'язок чотирьох факторів, пов'язаних зі здоровим способом життя (відмова від куріння, здорове харчування, регулярні фізичні вправи, індекс маси тіла <30 кг/м 2 ) та поширеністю множинного склерозу. Було обстежено 728 учасників з РС та 2 912 здорових учасників; отримані результати виявили, що люди, які дотримувались всіх чотирьох факторів здорового способу життя, показали на 71 % менший шанс розвитку множинного склерозу [14].…”
Section: результати обговоренняunclassified